Analysis of global asymptotic stability and pseudo almost periodic solution of a class of chaotic neural networks - Cherif, Farouk (Mathematical Modelling and Analysis, 2013)
In this paper we give sufficient conditions ensuring the existence and uniqueness of pseudo almost periodic solution of a class of delayed chaotic neural networks. Further, we study the global asymptotic stability (GAS) of the considered model and give a set of criteria on (GAS) by constructing new Lyapunov functional.